Gene flow from weedy rice to T1c-19 transgenic rice stacked with cry1C*/bar genes and fitness of F1 hybrids - Xie, Guang-Le; Shen, Jia-Qi; Wang, Min; Li, Ji-Kun; Huang, Yao; Qiang, Sheng; Song, Xiao-Ling; Dai, Wei-Min (Frontiers in Plant Science, 2025)
IntroductionBidirectional gene flow via pollen between transgenic rice and weedy rice could occur in natural fields. Gene flow from transgenic rice to weedy rice has been confirmed in many studies, and thus results showed that F1 hybrids could persist in natural agroecosystems due to their unimpaired reproductive ability. However, the reverse gene flow from weedy rice to transgenic rice is rarely reported.MethodWe quantified reverse gene flow from three weedy rice accessions to transgenic rice line T1c-19 with cry1C*/bar. In field trials with alternating layout of cultivating transgenic rice and weedy rice accessions and adjacent layout cultivating them in a close vicinity, the reverse gene flow was detected. And the fitness of reverse F1 (RF1) hybrids obtained by manual pollination using T1c-19 as maternal plants and weedy rice as paternal plants was evaluated in field.ResultNo gene flow from WRTZ was observed, while gene flows from WRMM were observed at 0.0508% and 0.0808%, respectively, and those from WRYY were 0.0692% and 0.1008%, respectively. RF1 plants exhibited significantly higher composite fitness compared to their weedy rice counterparts, due to enhanced fecundity-related traits observed under both insect pressure and no-insect pressure conditions. However, the impact of reverse gene flow may be limited because RF1 hybrid seeds presented lower seed shattering, and therefore most of it would be harvested by combine harvester.DiscussionOur study revealed that gene flow from three weedy rice accessions to T1c-19 could produce RF1 hybrids with greater composite fitness. Any loss of seeds into agroecosystem may result in a greater risk of RF1 hybrids due to their morphological similarity and high fitness.